Psychometric Properties Evaluation of Mental Health:Depression, Anxiety and Stress Scale (DASS) andSubjective Cognitive Decline Questionnaire (SCD-Q) at Millenial and Gen Z Employee in Indonesia - Reny Yuniasanti; Dewi Soerna Anggraeni; Sheilla Varadhila Peristianto; Sri Muliati Abdullah; Nina Fitriana; Martaria Rizky Rinaldi (Insight: Jurnal Ilmiah Psikologi, 2025)
Research data states that 37% of employees in Indonesia experience mental disorders, especially in the millennial and Z generations. Various terms and measurements of mental health often appear in psychological research but are rarely adjusted to respondents in the context of work settings and often limited to understanding the affective side of individuals, and not much is interpreted from the cognitive side. This is the primary basis for the translation and adaptation process, which uses measurements using the Depression, Anxiety, and Stress Scale (DASS-42) and Subjective Cognitive Decline Questionnaire (SCD-Q). The translation and adaptation process is carried out using Beaton's concept, which consists of the translation process, synthesis, back translation, expert committee review, pilot test, and the last stage is the submission developer committee. The respondents used in this process numbered 100 people according to the characteristics that have been determined. The DASS-42 item discrimination test results for the Stress are 0.685 - 0.879, the Anxiety is 0.701 - 0.989, and the Depression is 0.591 -0.841. Reliability with Cronbach Alpha for the Stress is 0.957, the Anxiety is 0.961, and the Depression is 0.935, which indicates high reliability. The results of the item discrimination test for the SCD-Q are 0.401-0.770 with a Cronbach Alpha of 0.926, which indicates high reliability. The measurement results show that the test tools for measuring mental health, DASS-42, and SCD-Q, can be used to measure and explore levels and analyze mental health in the work environment context, especially for the millennial and Z generations